Motives of sharing fake news and effects on mental health of social media users: a meta-analysis - He Dan,; Shahrul Nazmi Sannusi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
After the outbreak of COVID-19, the world faced various economic, health, and social challenges alongside terror from fake news and posts on social media. There has been a significant impact from the spread and sharing of fake news on the mental health of social media users. Henceforth, this study examined this issue within the context of uses and gratification theory. In doing so, the study performed a meta-analysis using cross-sectional studies regarding social media usage and the association between use and gratification among social media users. Fifteen articles from 2010 to 2020 were retrieved and finalised through strict selection criteria from Google Scholar, PubMed, and Web of Science. A random effect model was deployed to estimate the uses and gratification achieved from social media usage and the motivation behind sharing specific posts. The selected articles suggested a positive and significant role of the uses and gratification perspective in motivating users to select specific social media platforms to create and share posts. It was also identified that gratification can result from the performance of both positive and negative actions on social media by social media users. This study offers new insights into social media usage from the uses and gratification perspective during health crises, shedding light on its impact on fake news dissemination and suggesting practical algorithmic control measures.